Attacks on humans in Sweden by bear, wolf, lynx, wolverine, moose and wild boar in relation to Swedes’ fear for these animals - Sernert, Henriette (SLU/Dept. of Animal Environment and Health, 2011)
It is not easy to understand people’s fears since they are not always a logical reflection of the danger in certain situations. This study is an attempt to give a scientific view of the potential danger that certain animals in Sweden pose and compare this to Swedes’ fear of these animals. A report shows that Swedes’ have a certain amount of fear for being attacked by a wild animal in the forest and this fear has increased for certain animals over the last years. It would therefore be of interest to see if this fear is warranted and if the most feared animals are the ones that pose the biggest threat. In comparison with other dangers in our society none of these animals seems to pose any considerably large threat to us. Brown bear, wild boar and moose are the ones that could be considered as a threat, if any, because these are the ones that from time to time attack humans. This study is meant to inspire more scientific research about fear and attacks from different animals and hopefully lessen some of the fear that exists for these animals. Also to elucidate the problem about being afraid of getting attacked and recommend more information about these animals, the danger they pose and how to behave when meeting them in the forest. Människors rädsla kan ibland vara svår att förstå, speciellt när den inte är proportionerlig med den verkliga fara som en situation kan utgöra. Denna studie är ett försök till att ge en vetenskaplig bild över potentiella faror som vissa av våra svenska djur kan utgöra för oss människor och jämföra det med den rädsla som finns för dessa djur. En rapport från Sverige visar att det idag finns en rädsla för att bli attackerad av vilda djur i skogen och att denna rädsla har ökat under senaste åren. Det är därför av intresse att se om denna rädsla är befogad i förhållande till hur många attacker som sker och om den art som ligger till grund för mest rädsla är den art som utgör det största hotet. I jämförelse med andra faror i vårt samhälle kan inga av dessa djur ses som något större hot mot ...